2014
DOI: 10.1016/j.jobaz.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of royal jelly on aorta CD3, CD68 and eNOS expression in hypercholesterolaemic rats

Abstract: Hypercholesterolaemia (HPC) is a risk factor of cardiovascular disease. Synthetic medicines cause serious side effects that cause an imbalance in the body's functions. Therefore utilization of natural compounds could be an alternative concept in the treatment of diseases, as they have no side effects on human health. The present work is designed to evaluate the immunomodulatory role of royal jelly (RJ) on the aorta in hypercholestrolaemic rats.Cholesterol (30 mg/kg/day) administration for two months caused a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Administration of RJ to mixture treated rats caused a reduction in the levels of triglyceride (TG), total cholesterol (TC), LDL, VLDL and ratios of TC/HDL and LDL/HDL with marked elevation of HDL. Our results are in agreement with pervious study (42) . The improvement in lipid profile by RJ treatment may be due to RJ exhibited antihypercholesterolemic and antioxidant properties (43) .…”
Section: Discussionsupporting
confidence: 94%
“…Administration of RJ to mixture treated rats caused a reduction in the levels of triglyceride (TG), total cholesterol (TC), LDL, VLDL and ratios of TC/HDL and LDL/HDL with marked elevation of HDL. Our results are in agreement with pervious study (42) . The improvement in lipid profile by RJ treatment may be due to RJ exhibited antihypercholesterolemic and antioxidant properties (43) .…”
Section: Discussionsupporting
confidence: 94%
“…RJ is a mixture of free amino acids, proteins, sugars, lipids, vitamins, and minerals (Ahmed et al, 2014). RJ exhibits anti-oxidant (Abdel-Hafez et al, 2017), anti-inflammatory (Karaca et al, 2012), immunomodulatory (El-Nekeety et al, 2007), anti-tumor (Zhang et al, 2017), anti-hypercholesterolemic (Ibrahim, 2014), anti-microbial (Chan et al, 2009) and anti-allergic (Oka et al, 2001) activities. Moreover, RJ has shown neuroprotective effects in stress-induced animal models (Teixeira et al, 2017), aging (Pyrzanowska et al, 2014), and drug-induced neurotoxicity (Mohamed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of this study, administration of RJ was found to decrease the level of NO and enhance the TAC across the groups treated with it. Other researchers’ reports also stated that RJ administration decreases NO ( 31 32 ). Another study showed that the administration of RJ in mice, in which cardiac toxicity was induced by paclitaxel, significantly reduced NO production and increased levels of TAC ( 18 ).…”
Section: Discussionmentioning
confidence: 95%